Sequential Treatment from Mandibulectomy to Reconstruction on Mandibular Oral Squamous Cell Carcinoma Patients: Two Cases Report and Literature Review - Kwon, Jin-Ju; Ma, Yoon-Hee; Hwang, Dae-Seok; Ryu, MiHeon; Kim, Uk-Kyu (The Korean Journal of Oral and Maxillofacial Pathology, 2021)
Worldwide, oral cancer accounts for 2%–4% of all cancer cases. It is estimated that more of 90% of all oral neoplasms are oral squamous cell carcinoma (OSCC). The aims of this study were to evaluate follow-up outcomes in patients with OSCC invading the mandibular body bone who underwent primary radical resection and reconstructive surgery by fibular free flap or CAD-CAM T-mesh with pathological study on two cases. In this article, two cases of mandibular reconstruction in patients with OSCC invading the mandibular body bone are reported. A 68-year-old male patient visited the authors’ clinic with pain on the left mandibular region. After wide excision and segmental mandibulectomy on the mandibular OSCC, a enterocutaneous fibular free flap from right leg was used to cover the intraoral mucosal defect. The other 51-year-old female patient visited the authors’ clinic with pain on the right mandibular region. After wide excision and segmental mandibulectomy on the mandibular OSCC, reconstruction was done with a reconstruction plate and a fibula free flap from right leg. Unfortunately, fibular free flap was lost due to infection of the flap at post-operative 1month, secondary reconstruction using a custom-made type T-mesh and iliac PCBM was done to repair on the mandibular defect after four years postoperatively. The customized CAD-CAM T-mesh was made prior to the operation according to mirror image of remained jaw. Patients with OSCC invading the mandibular body bone are required an accurate segmental mandibulectomy immediate reconstructive surgery with various methods and followed by adjuvant radiation with or without chemotherapy in order to improve the quality of life through the restoration of the oral function and esthetics after surgery. Postoperative CCRT was determined according to the final pathologic findings such as lymph node metastasis and main lesion free margin safety, and this has an essential relationship in the prognosis of postoperative recurrence. We reviewed reliable treatment options on two patients of OSCC in mandible with pathologic findings KCI Citation Count: 0